Between Regulatory and Autonomy‐Based Private Law. Issue 5 (September 2016) - Dagan, Hanoch
Abstract: The emergent European Regulatory Private Law (ERPL) can be interpreted as a set of instruments in the service of collectivist aims and thus a radical departure of EU law from private law; but it need not. This article offers a competing interpretation of the three core pillars of ERPL: its reliance on the notion of regulated autonomy, its endorsement of access justice as a normative basis and its critique of the public/private distinction as it relates to EU law. ERPL in my reconstruction is a model for a private law system that embraces the liberal commitments to self‐determination, and thus, substantive equality, as its underlying normative infrastructure, is not overly embedded in the adjudicatory model and is sensitive to public concerns. Regulated autonomy and access justice, in this view, are local manifestations of the prescription of relational justice, which stands at the core of an autonomy‐based private law, properly interpreted. This understanding, I claim, is both normatively and jurisprudentially attractive; it is also particularly befitting to our transnational era, because it provides a non‐statist foundation for the prescriptions of non‐discrimination and accommodation.